2021
DOI: 10.7150/jca.56135
|View full text |Cite
|
Sign up to set email alerts
|

CREBBP knockdown suppressed proliferation and promoted chemo-sensitivity via PERK-mediated unfolded protein response in ovarian cancer

Abstract: CREBBP, in short CBP, has been reported to be involved in tumorigenesis in various cancers, but its role in ovarian cancer remains largely unexplored. In our study, survival analysis of CBP in patients with ovarian cancer was conducted using the Kaplan-Meier Plotter database, then we utilized specific shRNA targeting CREBBP to block the expression of CBP, and detected its effect on cell proliferation and chemo-sensitivity in ovarian cancer cells. The results showed that high expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similarly, our findings also revealed that high CREBBP expression was associated with a favorable HNSCC prognosis, indicating that CREBBP might play a tumor-suppressive role in HNSCC. However, Hu et al demonstrated that CREBBP acted as an oncogene and predicted a poor prognosis in ovarian cancer [ 37 ]. These differences might be due to tumor heterogeneity among different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our findings also revealed that high CREBBP expression was associated with a favorable HNSCC prognosis, indicating that CREBBP might play a tumor-suppressive role in HNSCC. However, Hu et al demonstrated that CREBBP acted as an oncogene and predicted a poor prognosis in ovarian cancer [ 37 ]. These differences might be due to tumor heterogeneity among different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Among OCCC CNV gains events, ARID1B, ARID1A1, and ASXL1 are associated with chromatin remodeling and modification. In novel identified CNV events of OCCC, CREBBP is involved in tumorigenesis in various cancers, and knockdown CREBBP can promote chemo-sensitivity in ovarian cancer cells ( Hu et al, 2021 ), while EPHA2 is associated with platinum-resistant in HGSOC, and RSK inhibitors effectively sensitized cells with EphA2 high to the therapy-induced apoptosis ( Moyano-Galceran et al, 2020 ), LRP1B can act as a predictor of response to pegylated liposomal doxorubicin for ovary cancer ( Dionisio de Sousa et al, 2021 ). These results provided more potential targets for OCCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…SLC9A2 (solute carrier family 9, member 2 of subfamily A) has been reported to be drug resistant in OC cell lines [ 42 ]. STC2 (stanniocalcin 2) has been reported to participate in tumor proliferation in vitro and in vivo [ 43 ]. TBP (TATA box binding protein) has been reported to participate in the transcriptional regulation of OC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%